EEC and the Caribbean - Bourke, Gerald (EEC BrusselsBE, 1986)
Recaps history of Europe's relations with the Caribbean since the 1940's and reviews aspects of economy of various Caribbean States. Discusses efforts at regional cooperation in the Caribbean and EEC assistance to projects relating to food production, transport and communications, tourism, training and research. Outlines EEC assistance to national development projects in individual Caribbean territories. Assesses benefits of banana and sugar protocols, and the STABEX and SYSMIN systems to individual Caribbean territories in area of trade. Discusses contents of and prospects for Lome III.